Zmiany oczne u pacjentów po przeszczepieniu szpiku kostnego – prezentacja przypadków - Karwacka, Ewa; Ołdakowska-Jedynak, Urszula; Pączek, Leszek; Kęcik, Dariusz; Brydak-Godowska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
We present two cases of patients who developed keratitis sicca (dry eyes) and pemphigoid-like symptoms after allogeneic bone marrow transplantation. Skin biopsy revealed changes typical of GVHD. In both cases immunosuppressive treatment, systemic and local, produced improvement of the clinical condition.